Host Metabolic Disorders Induced by Alterations in Intestinal Flora under Dietary Pesticide Exposure - Liu, Jingkun; Zhao, Fangfang; Wang, Tianrun; Xu, Yanyang; Qiu, Jing; Qian, Yongzhong (Journal of agricultural and food chemistry, 2021)
A dietary pesticide residue causes underestimated influences on body health. In this work, experimental mice were exposed to commonly used pesticides that cause insulin resistance, inflammation, and non-alcoholic fatty liver diseases. Alterations in intestinal flora were detected in the exposure groups. The abundance of the flora causing high endotoxin production was intensively increased and led to body inflammation. High Firmicutes/Bacteroidetes and obesity-related flora characteristics were also found. The metabolisms of intestinal flora and host circulation were investigated through metabolomics. The associations of flora with their metabolites and host circulation were also established. Association analysis can determine the influences of pesticide exposure on such a complex system. The affected metabolic pathways in the liver were also determined to clarify the mechanism underlying the effect of pesticide exposure on host physiology. Interventions with fructooligosaccharides and fecal microbiota transplantation alleviated the metabolic disorders, thus directly confirming that the intestinal flora mediates the effects of pesticide exposure on host circulation. This work elucidated the intestinal-flora-mediated effects of dietary pollutant exposure on body health and provided potential measures for regulating flora and host circulation.